Answer:
The value of the variable x is -2 and the value of the variable y is -7.
Step-by-step explanation:
The substitution method consists of:
In this case, you have the system of equations:
[tex]\left \{ {{2*x-3*y=17} \atop {-3*x+y=-1}} \right.[/tex]
Isolating the variable y from the second equation:
y= -1 +3*x
Replacing this expression in the first equation:
2*x-3*( -1 +3*x)= 17
Solving:
2*x -3*(-1)-3*3*x= 17
2*x +3 -9*x= 17
2*x -9*x= 17 -3
(-7)*x= 14
x= 14÷(-7)
x= -2
Now, replacing the value of x in the expression y = -1 + 3 * x you get:
y= -1 +3*(-2)
Solving:
y= -1 -6
y= -7
So, the value of the variable x is -2 and the value of the variable y is -7.